Pengalaman Komunikasi Interpersonal Orang Tua Dan Anak Usia 8-10 Tahun Dalam Memahami Dampak Dari Bermain Game Online Dan Dampaknya Terhadap Prestasi Di Sekolah - Mira Renata; Robby Rachman Nurdiantara; Taufiq Furqon Nurhakim (KOMVERSAL, 2023)
This study aims to find out the experience of interpersonal communication between parents and children 8-10 years old, to understanding the impact of playing online games and the impact on their achievement at the schools in Bandung. The type of this research used is a qualitative descriptive study, and data analysis used are data reduction, data presentation and conclusions or verification. The results showed that parents were not able to have good interpersonal communication with their children, they tend to be aggressive and reactive, to deal with online game addiction that happened to their son, they look confused and don't know how to deal with this problem, so that they can only scold their children and forbid them to play online games, without being able to communicate effectively with them. Furthermore, playing online games has a negative impact on children, among others, the negative psychological, physical and behavioral impact for them, such as they are forgetting the time, not focused and don't listen to the parents, then forget about the environment because the are too fun playing games on their cellphone alone, emotional if they lose playing games, sleep late and forgot to eat. they don't want to listen to parents suggestions and orders also, and their school performance has decreased Keywords: Communication1, Interpersonal2, Games Online3, Performance4